ANALISIS WAKTU KELULUSAN MAHASISWA DENGAN METODE CHAID (STUDI KASUS: FMIPA UNIVERSITAS UDAYANA) - PADMINI, IDA AYU SRI; SUCIPTAWATI, LUH PUTU; SUSILAWATI, MADE (E-Jurnal Matematika, 2012)
This research aim to knowing the variables classification that distinguish graduated time student between proper time with not proper time on FMIPA Udayana Universities with use CHAID Method. This research conducted at FMIPA Udayana Universities, with research sample about 751 persons student graduated FMIPA Udayana Universities period February 2008 until August 2011. CHAID method produce 7 segment there are: student graduated from Biology department and Chemistry women gender; from Biology and Chemistry man gender; from Mathematic department and Physic with IPK?3,00; from Mathematic department and Physic with IPK>3,00 and thesis period?6 months; from Mathematic department and Physic with IPK>3,00 and period thesis>6 months; from Pharmacy as well as student graduated from Computer science department.
Keywords: CHAID Method; Student Graduated Time; Proper Time; Not Proper Time